Surgery for lung cancer as the second primary malignancy - Krasauskas, Arnoldas; Aškinis, Renatas; Zaremba, Sigitas; Smailytė, Giedrė; Cicėnas, Saulius (Acta medica Lituanica, 2013)
Following a successful treatment of the first oncological disease, the second malignancy can develop. This retrospective study was designed to evaluate the efficacy of surgical treatment results for patients with the second primary lung cancer (2PLC) depending on the site of the first primary tumor (1PT). Materials and methods. From 2005 to 2009, 88 patients (pts) were treated in the Subdivision of Thoracic Surgery and Oncology, Institute of Oncology, Vilnius University, with lung cancer as the second primary malignancy. 29 patients (33%) underwent surgery: 17  pts (58.6%)  –  lobectomies, 2  pts (6.9%) – pneumonectomies, 9 pts (31%) – anatomical segmentectomies and 1 pt (3.5%) – bilobectomy. All lung resections were performed with lymph nodes dissection. We had neither major complications nor mortality 30 days after surgery. Stages of 2PLC were as follows: IA-B stage (st.) – 19 pts (65.5%), IIA-B st. – 7 pts (24.1%), and IIIA-IV st. – 3 pts (10.3%). Lung cancer morphology was the following: squamous cell – 11 pts (37.9%), adenocarcinoma – 13 pts (44.8%), large cell carcinoma – 4 pts (13.8%), small cell lung cancer – 1 pt (3.5%). First primaries of the patients were as follows: larynx – 6 pts (207%), lung – 2 pts (6.9%), stomach – 3 pts (10.3%), colon and rectum – 4 pts (13.8%), kidney – 4 pts (13.8%), prostate – 4 pts (13.8%), breast – 2 pts (6.9%), gynecology – 2 pts (6.9%) and haematologic malignancies – 2 pts (6.9%). According to 1PT localization patients were divided into 4 groups: airways, gastrointestinal, urology and other malignancies. Results. 1- and 3-year survival was 69% and 27.6% (60.9% and 30.4% for males; 27.6% and 16.7% for females). 3-year survival for the first primary cancer was 37.5% in urological cancers, 14.3% in gastrointestinal, 37.5% in airway cancers and 16.7% in other cancer cases. Survival by stage of 2PLC was as follows: IA-B st. – 33.3%, IIA-B st. – 28.6%, respectively. No patients survived for 3 years with IIIA-IV st. of 2  PLC. By morphology of 2 PLC there were adenocarcinoma cases in 14.3%, squamous cell carcinoma in 50.0%. One patient with small cell 2 PLC has lived so far. Conclusions. 1. The site of the first primary tumor is not a significant prognostic factor for surgical outcomes of the second primary lung cancer (p > 0.5). 2. Statistically significant survival rates did not differ by gender and histological type of 2PLC. 3. A statistically significant survival difference was obtained only between the patients with IA-IIB st. and IIIA-IV st. of 2PLC (p = 0.0013).
Keywords: surgical treatment; second primary lung cancer